Microbiota and mycotoxins in traditional beer of the greater Kimberley area and associated brewing and consumption practices - Ikalafeng, Bridget Keromamang (Bloemfontein : Central University of Technology, Free State, 2008)
The purpose of this study was to evaluate brewing and consumption practices and to screen for micro-organisms and mycotoxins associated with traditional beer produced and consumed in the marginal urban settlements of the city of Kimberley in the Northern Cape Province of South Africa. The survey study revealed that traditional beer is no longer being brewed for traditional purposes only, as was the case in the past, but rather for commercial gain. Both brewers and consumers, however, appeared to be largely unaware of disease-causing micro-organisms present on the hands or bodies of handlers that can be transferred to the beverage during the handling process, and were seemingly not conversant with regard to the effects of hazardous ingredients sometimes incorporated during the brewing process. Unemployment and a lack of education emerged as pivotal factors related to the production of traditional beer and the ignorance of the associated safety thereof. The survey further indicated that although facilities such as the availability of potable water (taps in yards) and flushing toilets were sometimes in place, other facilities such as basins with hot running water were often not available. In commercially produced and homebrewed traditional beer the mean counts for total coliforms and Staphylococcus spp. were circa 105 cfu.ml-1 whereas the TVC (Total Viable Counts) and total fungi counts were 106 and 107 cfu.ml-1 respectively. The total coliforms and Staphylococcus spp. counts for homebrewed traditional beer were approximately one log-phase higher than the commercial version. The counts in the homebrewed beer probably originated from contamination during handling, while in the commercial product contamination originated either in the raw ingredients or during postprocessing and consumption. Apart from staphylococci, considerable numbers of total coliforms indicating faecal contamination were noted. A rapid, easy, reliable and accurate technique that could be used to quantify the level of mycotoxins (deoxynivalenol and citrinin) in the beer was developed through validation of the ELISA Ridascreen methodology. Using this method, the deoxynivalenol (DON) level in the beer samples was found to exceed the recommended levels suggested by the European Union, while citrinin levels in the samples varied between 35.6 ppb and 942.2 ppb. In the case of citrinin there were statistically significant differences between spring, summer and winter samples, confirming the seasonal impact on fungal growth and consequent mycotoxin production. An R2-value of 0.409 was noted between DON and citrinin, indicating a weak positive association. Finally, an awareness programme in the format of a poster with accompanying subscripts was developed to address issues of safety and hygiene of traditional beer in the study area. The poster utilises animatedstyle colour images of selected practices that need to be addressed, accompanied by slogans summarising the particular image in English, Afrikaans and Setswana. It is envisaged that, as part of a comprehensive awareness programme, the poster will contribute greatly to the quality, safety and promotion of traditional beer in the area.
Thesis (D. Tech.) -- Central University of Technology, Free State, 2008
Keywords: Central University of Technology, Free State - Dissertations; Mycotoxins; Mycotoxicoses; Brewing microbiology - South Africa - Kimberley; Beer - Quality control - South Africa - Kimberley; Brewing - Quality control - South Africa - Kimberley; Drinking of alcoholic beverages - South Africa - Kimberley - Statistics; Alcoholic beverage industry - South Africa - Kimberley - Statistics; Dissertations, academic - South Africa - Bloemfontein